Essays in the economics of education - Abington, Casey (Kansas State University, 2010)
The first essay examines the allocation of education spending. Human capital investment in early childhood can lead to large and persistent gains. Beyond this window of opportunity, human capital accumulation is more costly. Despite this, government education spending is allocated disproportionately toward late childhood and young adulthood. The consequences of a reallocation are examined using an overlapping generations model with private and public spending on early and late childhood education. Taking as given the higher returns to early investment, the model shows the current allocation may nonetheless be appropriate. With a homogeneous population, this can hold for moderate levels of government spending. With heterogeneity, this can hold for middle income workers. Lower income workers, by contrast, may benefit from a reallocation. The second essay provides a detailed review of the human capital proxies used in growth regressions. Economic theory and intuition tells us that human capital is important for economic growth, and now most empirical growth studies include a human capital component. Human capital is a complex concept that is difficult to quantify in a single measure. A number of proxies have been proposed, with most focusing on an aspect of education. The consensus is that human capital is poorly proxied. For each of the most commonly used measures, I give a description, discuss trends, summarize the literature and results, compare advantages and disadvantages, and list data sets. This review will serve as a useful reference for any researcher including human capital in a growth regression. The final essay explores the importance of a variety of human capital measures for growth using the Bayesian Averaging of Classical Estimates (BACE) approach proposed by Sala-i-Martin, Doppelhofer, and Miller (2004). BACE combines standard Bayesian methods with the classical approach to address the problem of model uncertainty. A new data set is constructed that includes 35 human capital variables. The analysis shows that multiple human capital measures are robustly significant for growth. Some of these variables are IQ scores, the duration of primary and secondary education, average years of primary education, average years of female higher education, and higher education enrollment.
Keywords: Human capital; Education; Economic growth; Economics, General (0501)